The «Islamic State»: trajectory and reach a year after its self proclamation as a «Caliphate» - Tomé, Luis (2015)
On 29 June 2014, the ISIS/ISIL or Daesh announced the change of its name to just "Islamic State" (IS), proclaimed itself a "Caliphate" and named its leader Abu Bakr al-Baghdadi as "Caliph Ibrahim". About a year later, this article intends to evaluate the trajectory and reach of this territorial jihadist entity. It starts by contextualizing the self-proclamation in terms of ideology and objectives and then it describes how the IS has sought to consolidate itself as a de facto "State" and the tragic effects of its policy of terror. The last part examines the international expansion of the IS, analysing its reach in attracting "foreign fighters", the new wilayats created outside Syria and Iraq, the newly affiliated local groups, and the activities of the IS in cyberspace.